Concentration-runoff relationships of contrasting small mountainous rivers in the Pacific Northwest, USA: Insights into the weathering of rhenium relative to other weathering products. (15th November 2022) - Ghazi, Layla; Goñi, Miguel; Haley, Brian A.; Muratli, Jesse M.; Pett-Ridge, Julie C.
Abstract: This study examines dissolved rhenium (Re) concentrations as a function of water runoff using river samples from two contrasting mountainous watersheds, the Eel and Umpqua Rivers in the Pacific Northwest, USA. These watersheds share many key characteristics in terms of size, discharge, climate, and vegetation, but they have a 15-fold difference in sediment yield due to differences in their tectonic setting and uplift and erosion rates. We evaluate concentration-runoff (C-R) relationships and ratios of coefficients of variation (CVC /CVR ) for major cations, anions, dissolved inorganic carbon, selected trace elements including Re, and 87 Sr/ 86 Sr ratios. Recent research outlines the potential of Re to serve as a tracer for the oxidation of ancient/fossil organic matter because of its close association with petrogenic carbon (OCpetro ) in rocks. In both the Eel and Umpqua Rivers, our measurements show that Re behaves similarly to major weathering derived-solutes corrected for atmospheric input, such as Ca 2+ *, Mg 2+ *, and Na + * with modest dilution across all tributaries with increasing runoff. Rhenium behaves dissimilarly from other trace elements, such as Mo and U, and is also dissimilar to biologically-cycled nutrients, such as NO3 –, PO4 3−, and K + *, suggesting differences in sources, solute generation mechanisms, and flowpaths. Rhenium behavior is also distinct from that of colloids, which have increasing concentrations with increasing runoff. We find that Re and sulfate corrected for atmospheric input (SO4 2− *) have distinct C-R relationships, in which SO4 2− * undergoes greater dilution with increasing runoff. This implies that Re is not dominantly sourced from sulfide weathering, which leaves primary bedrock minerals and OCpetro hosted in bedrock of these watersheds as the likely dominant sources of dissolved Re release. At mean discharge, Re concentration in the Eel river (3.5 pmol L -1 ) is more than two times greater than Re concentrations in the Umpqua River (1.5 pmol L -1 ). Furthermore, comparison of two tributary watersheds with similar bedrock but marked differences in erosion rates show higher Re concentrations in Bull Creek (erosion rate of 0.5 mm yr −1 ) relative to Elder Creek (erosion rate of 0.2 mm yr −1 ). The results of this study suggest that dissolved Re in the Eel and Umpqua River basins is likely derived from primary mineral dissolution or OCpetro oxidation, and Re fluxes are higher in areas with higher erosion rates, suggesting that tectonic setting is one factor that controls Re release and therefore OCpetro oxidation.